Speech language pathologists’ self-report on counselling - Manzoor, Saadia; Awais Butt, Ghazal; Mukhtar, Tehreem; Afzal, Binash; Noreen, Hafsa (Journal of the Pakistan Medical Association, 2022)
Objective: To determine the level of understanding among speech language pathologists regarding counselling. Method: The cross-sectional study was conducted online from July 2020 to January 2021, and comprised speech language pathologists of either gender working in public or private institutions or clinics of Punjab, Sindh and KPK. Data was collected using the Self-report on counselling and interpersonal communication skills’ questionnaire. The collected data was analysed using SPSS 22. Results: Of the 190 subjects, 176(92.6%) were females and 14(7.4%) were males. Majority 173(91.1%) were aged 25-35 years, and 173(91.1%) belonged to the Punjab province. Majority 175(92%) of the respondents reported satisfaction about their own counselling skills, while 168(88.4%) also expressed the need for inclusion of more courses and training to develop counselling and interpersonal communication skills. Conclusion: With experience, professional counselling skills improve and awareness about the need to incorporate counselling training also increases. Key Words: Counselling, Pakistan, Programme, Self report.